Incessant left ventricular tachycardia of unusual etiology - Praloy Chakraborty; H.S. Isser; Sudheer Arava; Kausik Mandal (Indian Pacing and Electrophysiology Journal, 2016)
Apart from Coronary artery disease, left ventricular tachycardia may result from cardiac sarcoidosis, left ventricular tumor, chagas disease and idiopathic left ventricular tachycardia. We report a rare case of incessant left ventricular tachycardia resulting from left dominant arrhythmogenic cardiomyopathy.